2000
DOI: 10.1111/j.1553-2712.2000.tb00517.x
|View full text |Cite
|
Sign up to set email alerts
|

Pantomography vs Mandibular Series for the Detection of Mandibular Fractures

Abstract: Abstract. Objective: The two primary radiographic techniques used for the evaluation of mandible injury are a pantomographic series (PS) and the standard four-view mandibular series (MS). Despite a tenuous foundation, there is apparent bias in favor of PS compared with MS. Many emergency departments do not have ready access to the specialized equipment necessary to perform a pantomographic study. The hypothesis of this study was that a high-quality standard MS is as sensitive and specific as a PS in the detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…For patients needing to stay supine with a collar on, only anteroposterior/lateral/oblique views are attainable,[ 69 ] with the main limitation here being that the condylar region is poorly visualized and displacement is difficult to assess. [ 69 70 ] An orthopantomogram, Clementscitsch, and posteroanterior views are unfeasible in this case given the person is unable to stand or move his/her neck; hence, in these patients, CT is the preferred modality by default.…”
Section: Discussion and Review Of Literaturementioning
confidence: 99%
“…For patients needing to stay supine with a collar on, only anteroposterior/lateral/oblique views are attainable,[ 69 ] with the main limitation here being that the condylar region is poorly visualized and displacement is difficult to assess. [ 69 70 ] An orthopantomogram, Clementscitsch, and posteroanterior views are unfeasible in this case given the person is unable to stand or move his/her neck; hence, in these patients, CT is the preferred modality by default.…”
Section: Discussion and Review Of Literaturementioning
confidence: 99%
“…A recently conducted study 20 that explored the diagnostic potential of these examinations based on clinical studies without a criterion standard to compare the observers' interpretations concluded that mandibular series performed superiorly to panoramic radiographs. We used cadaver specimens in order to be able to determine the ground truth so that the diagnostic accuracy for the imaging modalities of interest could be appropriately determined through an ROC analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have been clinical evaluations with no criterion standard other than the subjective opinions of an expert. 2,[20][21][22] Panoramic images have to be exposed appropriately in order for the technique to be diagnostically productive. The panoramic radiograph is very useful in that the entire mandible is adequately visualized if patient positioning and choice of exposure parameters are adequate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations